Foundations of international migration law / edited by Brian Opeskin, Richard Perruchoud, Jillyanne Redpath-Cross. - Opeskin, Brian R.; Perruchoud, Richard; Redpath-Cross, Jillyanne (Cambridge University Press, 2012)
International migration law is an important field of international law, which has attracted exceptional interest in recent years. This book has been written from a wide variety of perspectives for those wanting to understand the legal framework that regulates migration. It is intended for students new to this field of study who seek an overview of its many components. It will also appeal to those who have focussed on a particular branch of international migration law but require an understanding of how their specialisation fits with other branches of the discipline. Written by migration law specialists and led by respected international experts, this volume draws upon the combined knowledge of international migration law and policy from academia; international, intergovernmental, regional and non-governmental organisations; and national governments. Additional features include case studies, maps, break-out boxes and references to resources which allow for a full understanding of the law in context.